Dynamics of occurrence of refractory coeliac disease and associated complications over 25 years. Issue 2 (25th November 2016) - Eigner, W.; Bashir, K.; Primas, C.; Kazemi‐Shirazi, L.; Wrba, F.; Trauner, M.; Vogelsang, H.
Summary: Background: Refractory coeliac disease, enteropathy associated T‐cell lymphoma and small bowel adenocarcinoma are rare but prognostically important complications in coeliac disease. Aim: To analyse potential changes in occurrence of complicated coeliac disease over the last 25 years. Methods: One thousand one hundred and thirty eight patients were included and evaluated based on their time of first presentation at the Medical University of Vienna, Austria. Occurrences of refractory coeliac disease and associated malignancies were evaluated for 5‐year intervals from January 1990 until December 2014 and were compared over time. Results: 2.6% ( n = 29) were diagnosed with refractory coeliac disease (females 65.6%, mean age at diagnosis 62.8 years). The proportion of those patients was 2.6%, 3.1%, 3.3%, 2.7% and 0.5% for the 5 year intervals from 1990 onwards. Thus, the number of refractory cases has been decreasing since 2000 ( P = 0.024). The number of patients presenting with lymphoma ( n = 7) was 0.6%, 0.4%, 1.1%, 0.8% and 0% from 1990 to 2014. Similarly the number of patients with adenocarcinoma ( n = 4) decreased to 0% until 2014. Overall mortality in patients suffering from refractory disease was 48%. Of all patients diagnosed with lymphoma 71.4% died with a 5‐year survival rate of 28.6%. Conclusions: Over the past 15 years the occurrence of complicated coeliac disease has been decreasing. This possibly reflects a higher awareness of coeliac disease and optimised diagnosis and treatment with avoidance of long‐term immunological disease activity. Symptomatic disease and a delay in diagnosis are risk factors for refractory coeliac disease and related cancer. Abstract : Linked Content This article is linked to Matuchansky and Eigner and Volgesang papers. To view these articles visit https://doi.org/10.1111/apt.13941 and https://doi.org/10.1111/apt.13966 .